Safety and efficacy of ontamalimab in inflammatory bowel disease: A systematic review and dose- response meta-analysis - Setyobudi, Assyadilla Kirana; Yudianto, Valentino Ryu; Hariftyani, Arisvia Sukma; Gatot Soegiarto (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Inflammatory bowel diseases (IBDs), such as Crohn’s disease and ulcerative colitis, involve chronic inflammation of the digestive tract. The incidence of IBD has been increasing globally, posing a growing burden despite advancements in treatment. Novel therapies targeting adhesion molecules such as MAdCAM-1 show promise by specifically inhibiting lymphocyte infiltration into the gut, potentially offering safer and more effective treatment options. This meta-analysis and systematic review were conducted to provide efficacy and safety analysis of ontamalimab for IBD treatment. Dose-response (DRMA), network (NMA), and random effect meta-analysis were conducted to extract clinical response, clinical remission, biomarker change, and adverse events of ontamalimab. Studies were retrieved from PubMed, Cochrane, and EMBASE to describe the pooled risk ratio (RR) and heterogeneity was determined if I2 >50%. RoB2 tool and ROBINS-I were used to assess risk of bias in RCT and clinical trial studies, respectively. The result was considered significant if p<0.05. A total of 670 studies were screened, resulting in 8 multicentre studies. There were significant differences in clinical response (RR: 1.39; 95%CI: 1.12–1.73; p = 0.003; I2= 35%), clinical remission (RR: 1.72; 95%CI: 1.17–2.53; p=0.006; I2= 26%), mean change of FC (RR: 624.29; 95%CI: 543.28-705.29; p<0.001; I2= 0%), mean change of CRP serum (RR: 9.71; 95%CI: 7.12–12.3; p<0.001), and mean MAdCAM-1 serum level (RR: 235.57; 95%CI: 203.80–267.33; p <0.001) between ontamalimab 75 mg and placebo after 12 wk of treatment. Meanwhile, adverse events from both groups were similar to those observed in patients treated with either placebo or ontamalimab. This study concluded that ontamalimab 75mg demonstrated significant efficacy in treating IBD, achieving superior outcomes in clinical response and clinical remission compared to placebo. Importantly, no cases of PML and significant adverse events were detected, indicating a favorable safety profile relative to other anti-MAdCAM-1 therapies.